The “regulatory idea” of the environmentalization process in the brazilian port corporate sector: identification and critical analysis - Rodrigues, Jondison Cardoso; Castro, Edna Maria Ramos de (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The environmental dimension has become a source of "concern" and actions from the port sector, through the formation of an environmental discourse as action (environmentalization). In considering the issue, the aim of this article is to identify and analyze critically the "regulative idea" that guides the process of environmentalization of the Brazilian port business sector, and consequently show the characteristics and forms of environmental actions that reproduce it. The methodological approach chosen was qualitative, whose research design proceeded in three stages: literature review, document research, and in addition, as corroborative element, a case study. The Port marketing and the challenge of the third generation port, from the United Nations Conference on Trade and Development (UNCTAD) of 1992, is a regulative idea, in which the assumption is grounded in conceptual models of ports, with the speech-guide of rapprochement and port-city integration, measures for environmental protection and respect for the environment and security. The characteristics of the playback operation concentrates on port workers in proactive capabilities, and in the use of environmental education. The critical analysis showed that the inclusion of the environmental dimension is a source of competitive advantage and corporate health, especially to sustain the insatiable logic of capital accumulation.